2016
DOI: 10.1177/1740774516679665
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the functions and operations of data monitoring committees: Survey and focus group findings

Abstract: Background: The use of data monitoring committees in the conduct of clinical trials has increased and evolved, but there is a lack of published information on when data monitoring committees are needed and utilized, the acceptable range of data monitoring committee practices, and appropriate qualifications of data monitoring committee members. Methods: To gain a better understanding of data monitoring committee operations and areas for improvement, the Clinical Trials Transformation Initiative conducted a surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 8 publications
0
23
0
2
Order By: Relevance
“…Although training is highly desirable prior to serving on a DMC, the vast majority of our survey respondents indicated that they had not received training and were unaware of DMC-specific training programs. 3 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although training is highly desirable prior to serving on a DMC, the vast majority of our survey respondents indicated that they had not received training and were unaware of DMC-specific training programs. 3 …”
Section: Resultsmentioning
confidence: 99%
“…sponsors, investigators, and institutional review boards); and (d) identify strategies for preparing the next generation of DMC members. 3 …”
Section: Introductionmentioning
confidence: 99%
“…Charter [..] should fully address whether the DMC will have access to unmasked data at the subject level and aggregate level. (Calis et al 2017;Lewis et al 2016) 2. Chen-Mok et al described the experiences and challenges in data monitoring for clinical trials within an international tropical disease research network:…”
Section: From the Us Department Of Health And Human Services (Dhhs) (mentioning
confidence: 99%
“…Committee members take on a substantial responsibility for the safety of participants in the study, those yet to be enrolled, and even those who might someday receive the intervention. Numerous challenges associated with this responsibility have been recently described, including the need for training for DMC members and clear DMC reports (Calis et al 2017b(Calis et al , 2017aDavis et al 2018;DeMets and Ellenberg 2016;DeMets and Fleming 2004;Ellenberg and Ellenberg 2018;Ellenberg et al 2002;Fleming et al 2017Fleming et al , 2018Lewis et al 2016;Neaton et al 2018). DMC reports are produced by an independent unmasked statistical team.…”
Section: Introductionmentioning
confidence: 99%